OPTIMIZATION OF GAS STATION SERVICE PERFORMANCE IN YOGYAKARTA CITY TO INCREASE COMPANY WORK PRODUCTIVITY - Nurjannah, Anisa; Amin, Muflikhul; Prakoso, Indro (Journal of Industrial Engineering Management, 2024)
Pertamina gas stations have an important role in the national economy. Optimizing performance in this sector is very necessary to improve Pertamina's internal performance, optimize state revenue, and increase customer satisfaction. At the motorcycle Pertalite filling work station, long queues often occur. This study aims to evaluate the current fuel filling work method, so that optimization analysis and improvement proposals can be carried out. The methods used are time study and MOST. The results of the time study from observations of 300 respondents from 15 gas stations in Yogyakarta are that the average working time of respondents is 33.78 seconds with a normal time of 33.19 seconds and a standard time of 44.85 seconds. While the results of processing using MOST obtained a TMU value of 810 if converted into seconds to 29.16 seconds. Furthermore, an analysis and improvement proposal were carried out which gave a working time result of 19 seconds, with a normal time of 18.62 seconds and a standard time of 25.19 seconds. Things that need to be improved in the process of filling Pertalite fuel for motorbikes are to prepare the motorbike with the seat and tank already open in 1 queue before the work station, make payments during the filling process, and move the motorbike immediately after the filling process is complete (closing the tank and seat is done outside the work station).